De gemeentelijke administratieve sancties in Brussel op de proef gesteld tijdens de coronacrisis - Diletta Tatti (Brussels Studies)
The measures adopted during the first lockdown from March to June 2020 were characterised by their unheard-of impact on the use public space. Previously harmless types of behaviour had been made into offences. From the beginning, the punishment of these offences was a priority for the Belgian authorities. In the Brussels Region, the municipal administrative sanctions (MAS) ensured this repressive approach in an unprecedented interrelation with criminal enforcement. Based on the analysis of quantitative and qualitative empirical data, this article examines the outlines and applications of this “exception for Brussels” in terms of issues related to the use of public space in a city characterised by significant socio-spatial inequalities.